2017
DOI: 10.3390/coatings7090145
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Assessment of Sericin-Silver Functionalized Silk Fabrics for Enhanced UV Protection and Antibacterial Properties Using Experimental Design

Abstract: Silk sericin (SS) was used as both a 3-dimensional matrix and reductant for the in situ synthesis of silver nanoparticles (AgNPs) finished on silk fabrics. We demonstrated enhanced UV protection and antibacterial properties using this synthesis which was an environmental friendly approach. Development and optimization was achieved using a central composite design (CCD) in conjunction with the response surface methodology (RSM). The goal was to identify the concentrations of SS and AgNO 3 that produced the opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Furthermore, the peaks ranging from 500 to 800 cm −1 suggested the presence of silver linkage with N atoms as detailed by other scientists. Many other scientists around the globe also described the same FTIR peaks, as in the present study, but some also reported slightly variable results [60–63]. The reason behind this deviation is not clear yet, and a further deep investigation is necessary.…”
Section: Discussionsupporting
confidence: 72%
“…Furthermore, the peaks ranging from 500 to 800 cm −1 suggested the presence of silver linkage with N atoms as detailed by other scientists. Many other scientists around the globe also described the same FTIR peaks, as in the present study, but some also reported slightly variable results [60–63]. The reason behind this deviation is not clear yet, and a further deep investigation is necessary.…”
Section: Discussionsupporting
confidence: 72%
“…However, most of the conventional syntheses require the use of hazardous chemicals and generate toxic organic byproducts. At present, a large number of exhaustive studies have focused on the biological synthesis of AgNPs using natural substances such as bacteria, fungi, proteins, polysaccharides, and plant extracts [5,13,14,15,16]. Considering the safety of biological synthesis process, the approaches involving plant extracts could generate much less contamination and have minimal impact on the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Silver nanoparticles (AgNPs), which are famous for broad-spectrum and high-efficient antibacterial effects due to their unique properties (e.g., nano-scale size, various shapes, and large surface area), have been widely used in many fields such as electronics, cosmetics, coatings, packaging, and biotechnology [ 5 , 6 , 7 ]. The synthesis and applications of AgNPs have already become a research hotspot in recent years [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The W CIE was calculated automatically, according to EN ISO 105-J02 [ 32 ]. Transmittance was measured with a UV/V is spectrophotometer Varian-Cary 50/Solascreen, using a software package to calculate specific UPF values using the in vitro method according to AS/NZS 4399:1996 [ 33 , 34 ]. UPF is an expression indicating the degree of protection against UV radiation and is calculated automatically from the transmittance T ( λ ), according to the following equation: where:…”
Section: Methodsmentioning
confidence: 99%